2002
DOI: 10.1007/s00221-002-1094-9
|View full text |Cite
|
Sign up to set email alerts
|

Increase in tibialis anterior motor cortex excitability following repetitive electrical stimulation of the common peroneal nerve

Abstract: The purpose of this study was to investigate whether repetitive electrical stimulation of the common peroneal nerve (CPN) is associated with changes in the motor response of the tibialis anterior (TA) muscle elicited by focal magnetic stimulation of the motor cortex. Motor evoked potentials (MEP) with a stimulation intensity of 125% of the threshold of the relaxed right TA were obtained before, during, and after repetitive electrical stimulation of the CPN (trains of five pulses of 1 ms, at a frequency of 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 41 publications
11
75
1
Order By: Relevance
“…Furthermore, if combined with a simple dorsi-flexion movement, these increases are evident after only 15 min of the intervention. A number of other protocols such as rTMS (Di Lazzaro et al 2002;Huang et al 2005) and repetitive electrical stimulation (Khaslavskaia and Sinkjaer 2005;Khaslavskaia et al 2002;Popovic et al 2003) have been implemented in the past to artificially induce cortical plasticity. The former of these two methods has the disadvantage of a slight but significant risk of inducing epileptiform seizures (Anand and Hotson 2002;Wassermann 1998).…”
Section: Functional Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, if combined with a simple dorsi-flexion movement, these increases are evident after only 15 min of the intervention. A number of other protocols such as rTMS (Di Lazzaro et al 2002;Huang et al 2005) and repetitive electrical stimulation (Khaslavskaia and Sinkjaer 2005;Khaslavskaia et al 2002;Popovic et al 2003) have been implemented in the past to artificially induce cortical plasticity. The former of these two methods has the disadvantage of a slight but significant risk of inducing epileptiform seizures (Anand and Hotson 2002;Wassermann 1998).…”
Section: Functional Significancementioning
confidence: 99%
“…The former of these two methods has the disadvantage of a slight but significant risk of inducing epileptiform seizures (Anand and Hotson 2002;Wassermann 1998). Such risks are not reported with rES; however, rES requires a higher number of stimuli to be delivered for significant effects to be observed (Khaslavskaia and Sinkjaer 2005;Khaslavskaia et al 2002;Popovic et al 2003). With the reduced number of stimuli and its proven effectiveness, PAS combined with a simple task seems an attractive rehabilitative tool.…”
Section: Functional Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have reported that simultaneous TENS and TOT augment balance performance7 and trunk control51 in subjects with stroke. Khaslavskaia and colleagues58 reported that cutaneous electrical stimulation over the common peroneal nerve for 30 minutes enhanced corticospinal excitability for up to 110 minutes in healthy adults, which supported the application of TENS before TOT. However, Khaslavskaia and Sinkjaer59 reported that cutaneous electrical stimulation applied over the common peroneal nerve combined with simultaneous active ankle dorsiflexion exercise for 30 minutes increased the motor evoked potentials recorded from the tibialis anterior by 66% in 8 healthy adults, whereas cutaneous electrical stimulation alone increased the motor evoked potentials by only 38% 59.…”
Section: Discussionmentioning
confidence: 86%
“…More recent findings suggest that the therapeutic effect of FES may be mediated by a strengthening of corticospinal connections to ankle dorsiflexor muscles such as the tibialis anterior (TA) [21,27]. There is evidence that repetitive FES alone (i.e., stimulation that is not paired with movement but applied while subjects were seated) can modulate corticospinal circuits controlling ankle dorsiflexion [28][29][30][31]. For example, motor-evoked potentials in the TA were increased by 30 min of repetitive stimulation of the common peroneal nerve (CPN) in subjects with SCI [29].…”
Section: Introductionmentioning
confidence: 99%